2007
DOI: 10.4049/jimmunol.179.2.1236
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-inflammatory Effects of Heat Shock Protein 72 Involve Inhibition of High-Mobility-Group Box 1 Release and Proinflammatory Function in Macrophages

Abstract: High-mobility-group box 1 (HMGB1), a nuclear protein, has recently been identified as an important mediator of local and systemic inflammatory diseases when released into the extracellular milieu. Anti-inflammatory regulation by the stress response is an effective autoprotective mechanism when the host encounters harmful stimuli, but the mechanism of action remains incompletely delineated. In this study, we demonstrate that increases in levels of a major stress-inducible protein, heat shock protein 72 (Hsp72) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 66 publications
3
98
0
Order By: Relevance
“…[42][43][44] It is well established that exogenous HMGB1 induces MEK-ERK activation in immune cells and cancer cells. 19,22,32,45 Here, we found that 3-MA inhibited HMGB1-induced phosphorylation of ERK, indicating that ERK is a downstream signal of PI3K. Importantly, knockdown or pharmacological inhibition of MEK-ERK attenuated HMGB1-induced LC3 conversion, suggesting that MEK-ERK is also required for HMGB1-induced autophagy in leukemia cells.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…[42][43][44] It is well established that exogenous HMGB1 induces MEK-ERK activation in immune cells and cancer cells. 19,22,32,45 Here, we found that 3-MA inhibited HMGB1-induced phosphorylation of ERK, indicating that ERK is a downstream signal of PI3K. Importantly, knockdown or pharmacological inhibition of MEK-ERK attenuated HMGB1-induced LC3 conversion, suggesting that MEK-ERK is also required for HMGB1-induced autophagy in leukemia cells.…”
Section: Discussionmentioning
confidence: 64%
“…Before immunoprecipitation, samples containing equal amounts of proteins were pre-cleared with Protein A or protein G agarose/sepharose (Millipore) (4 1C, 3 h) and subsequently incubated with various irrelevant immunoglobulin-G or specific antibodies (5 mg/ml) in the presence of protein A or G agarose/sepharose beads for 2 h or overnight at 4 1C while gently shaking. 16,17,19 Following incubation, agarose/ sepharose beads were washed extensively with phosphatebuffered saline and proteins eluted by boiling in 2 Â SDS sample buffer before SDS-polyacrylamide gel electrophoresis.…”
Section: Immunoprecipitation Analysismentioning
confidence: 99%
“…Proteins in cell lysates were first resolved by SDS-polyacrylamide gel electrophoresis and then transferred to nitrocellulose membrane and subsequently incubated with the primary antibody as previously described (20). After incubation with peroxidase-conjugated secondary antibodies, the signals were visualized using enhanced chemiluminescence according to the manufacturer's instruction.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…For example, HSP70 has an anti-inflammatory activity by means of its inhibition of nuclear factor kappa B (NF-B) and a resulting suppression of pro-inflammatory cytokine and chemokine expression (23)(24)(25)(26). HSP70 has been reported to stimulate base excision repair, possibly by activation of human AP endonuclease and DNA polymerase ␤ (27)(28)(29).…”
mentioning
confidence: 99%